Understanding suicidal ideation disparity between sexual minority and heterosexual Chinese young men: a multiple mediation model of social support sources, self-esteem, and depressive symptoms - Huang, Yiting; Liu, Jiayu; Huang, Gang; Zhu, Dejia; Zhou, Yunfei; Hu, Jingchu (Frontiers in Psychiatry, 2024)
Objectives: Although sexual minorities have reported higher levels of suicidal ideation than heterosexuals across cultures, the role of various psychosocial factors underlying this disparity among young men has been understudied, particularly in China. This study examined the multiple mediating effects of psychosocial factors between sexual orientation and suicidal ideation in Chinese sexual minority and heterosexual young men.Methods: 302 Chinese cisgender men who identified as gay or bisexual, and 250 cisgender heterosexual men (n=552, aged 18-39 years) completed an online questionnaire measuring perceived social support, self-esteem, depressive symptoms, and suicidal ideation. Results: Young sexual minority men reported significantly higher suicidal ideation and lower social support than their heterosexual peers. Structural equation modelling revealed two multiple indirect pathways. One pathway indicated that sexual orientation was indirectly related to suicidal ideation via family support and depressive symptoms. Another pathway indicated that sexual orientation was indirectly related to suicidal ideation via support from friends, self-esteem, and depressive symptoms. Conclusions: This study is among the first to examine the potentially cascading relationships between sexual orientation and psychosocial factors with suicidal ideation in a Chinese sample of young men. The findings highlight several promising psychosocial targets (i.e., improving family/friend support and increasing self-esteem) for suicide interventions among sexual minority males in China.